Direct anterior approach for total hip arthroplasty with patients in the lateral decubitus versus supine positions: A prospective, double-blinded, randomized clinical trial. (2nd February 2022) - Xiao, Yao; Li, Zhanglai; Feng, Eryou; Lin, Feitai; Zhang, Yiyuan; Weng, Yan; Chen, Jinhua
Purpose: The direct anterior approach (DAA) for total hip arthroplasty (THA) can be performed with patients in either in the lateral decubitus or supine position. Prompted by the lack of studies addressing differences between the two positions, this investigation aimed to examine clinical and radiographic outcomes and compare the lateral decubitus versus the supine position for THA using the DAA. Methods: Between January 1 and October 1, 2020, 90 patients who underwent primary unilateral THA using the DAA were recruited, with 54 (60%) undergoing THA in the supine position (SP group) and 36 (40%) in the lateral decubitus position (LP group). Technical information, clinical and radiographic outcomes, and patient-reported outcomes, including the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and Short-Form-12 (SF-12) were evaluated. All data were subjected to several statistical tests. Results: There were no preoperative differences in baseline characteristics between the LP and SP groups, which were also similar in terms of operative duration, length of hospital stay, and blood loss. Radiographic assessment confirmed satisfactory positioning of the prosthesis in both groups. There were no significant differences in terms of CK-MB and hemoglobin levels, Harris Hip Score, WOMAC, UCLA, visual analog scale score, and SF-12. The incidence of complications in the LP group was lower than in the SP group. Conclusion: Total hip arthroplasty performed via DAA in the LP and SP groups yielded excellent clinical outcomes, although the incidence of complications in the former was lower than in the latter.